Risk Factors for the Anal and Oral Human Papillomavirus (HPV) Infections among Women with Severe Cervical Lesions: A Prospective Case-Control Study - Džundová, Monika Nipčová; Sehnal, Borek; Zikán, Michal; Kocián, Roman; Dubová, Olga; Hubka, Petr; Dostálek, Lukáš; Kabele, Pavel; Brtnický, Tomáš; Slama, Jiri (Biomedicines, 2023)
The carcinogenicity of HPV infection in the anogenital and oropharyngeal regions is broadly accepted. The aim of the study was to define risk factors for anal and oral HPV infections in high-risk patients with biopsy-proven severe cervical lesions (CIN2+). Altogether immunocompetent 473 females with CIN2+ were categorized into the study group and another 245 women into the control group. The strongest risk factor for anal HPV infection was the presence of cervical HPV infection (p < 0.001). Furthermore, ten or more lifetime sexual partners (p = 0.013), a sexual non-coital contact with the anal area (p < 0.001), and actively practicing anal-penetrative intercourse (p < 0.001) were significantly associated with anal HPV. A history of genital warts in the woman (p = 0.010) and the presence of genital warts in the male partner (p = 0.029) were found statistically significant for the risk of oral HPV infection. Our data suggest that the presence of HPV infection, especially high-risk genotypes, in one anatomical site poses the greatest risk for HPV infection in another anatomical site. The cervix is the main reservoir of infection, but the risk factors for anal and oral HPV infections are dissimilar according to different anatomical distances and more complex routes of transmission.
Keywords: risk factors; CIN2+ patients; oral HPV; human papillomavirus; anal HPV; HPV infection